In the digital labyrinth: decentralized autonomous organizations (DAOS) and European private international law - López Rodríguez, Ana Mercedes (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The emergence of blockchain technology and so-called Decentralized Autonomous Organizations (DAOs) poses significant challenges for private international law. This paper examines the legal nature and regulatory framework of DAOs, exploring how their decentralized character, lack of traditional legal personality, and global operation impact their integration into different legal systems. Additionally, it discusses the difficulties in determining judicial jurisdiction and the applicable law in disputes related to these organizations, with a particular focus on Spanish and European Private international law. In this regard, the article addresses the limitations of traditional connecting factors, such as registered office or place of incorporation, and suggests solutions based on the territorial connections of the promoters, when feasible. Finally, it reflects on the need for regulation that integrates DAOs into the existing legal framework, ensuring a balance between technological innovation and legal certainty.